Sensitivity Analysis of Acoustic Field Parameters on a Change of Boundary Conditions in a Room - SUDER-DĘBSKA, Katarzyna; CZAJKA, Ireneusz; CZECHOWSKI, Mateusz (Archives of Acoustics, 2014)
The area of environmental protection concern minimises the impact that technical objects have on the environment. Usually the most effective way of protecting the environment is to influence the source of the problem. For this reason studies are conducted to modify the construction of machines, power machines in particular, so as to minimise their impact on the environment.In the case of environmental protection from noise it is most convenient to carry out measurements in an anechoic chamber. Unfortunately, this is possible only in very limited circumstances. In all other cases measurements are performed using an engineering method or the survey method, both of which are described in the standards and by taking into account the so-called environmental corrections. The obtained results are burdened with greater error than those of measurements in an anechoic chamber. Therefore, it would seem advantageous to develop a method of obtaining similar and reliable results as those in an anechoic chamber, but in a reverberant field. The authors decided to use numerical modelling for this purpose.The main objective of this work is a comprehensive analysis of the numerical model of a laboratory designed for acoustic tests of selected power machines. The geometry of a room comprising an area of analysis is easy to design. The main difficulty in modelling the phenomena occurring in the analysed area can be the lack of knowing the boundary conditions. Therefore, the authors made an attempt to analyse the sensitivity of various acoustic parameters in a room in order to change these boundary conditions depending on the sound absorption coefficient.